Efektifitas Pembelajaran Evaluasi Pendidikan Agama Kristen Di Sekolah Menengah Pertama (SMP) Kristen Jakarta Timu - Philipus Sunardi; Refni Fajar Wati Zega (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Learning effectiveness is the activeness and suitability in carrying outlearning for students and teachers as creators of this effectiveness in the learningprocess. There are many problems faced by teaching staff in delivering effectivelearning to their child participants. First, you must determine effective teachingtechniques to be taught and you must understand how to evaluate Christian religiouseducation. This certainly introduces the teacher's approach to evaluating and studentlearning outcomes.